Psychometric properties of the Chinese version of the oncology nurses health behaviors determinants scale: a cross-sectional study - Liu, Yuxiu; Zhang, Lan; Li, Shuzhen; Li, Hua; Huang, Yuqi (Frontiers in Public Health, 2024)
Objective To test the validity and reliability of the Oncology Nurses Health Behaviors Determinants Scale (HBDS-ON) in oncology nurses, the Chinese version was developed. Methods The Brislin double translation-back translation approach was employed to forward translation, back translation, synthesis, cross-cultural adaptation, and pre-survey, resulting in the first Chinese version of the Oncology Nurses Health Behaviors Determinants Scale (HBDS-ON). A convenience sample technique was used to select 350 study participants in Liaoning, Shandong, and Jiangsu, China, who satisfied the inclusion and exclusion criteria, to assess the validity and reliability of the scale. Results The Chinese version of the Oncology Nurses Health Behaviors Determinants Scale (HBDS-ON) had six subscales (perceived threat, perceived benefits, perceived barriers, self-efficacy, cues to action, and personal protective equipment availability and accessibility), including 29 items. The average scale level was 0.931, and the content validity level of the items varied from 0.857 to 1.000. Each Cronbach’s α coefficient had an acceptable internal consistency reliability range of 0.806 to 0.902. X2/df = 1.667, RMSEA = 0.044, RMR = 0.018, CFI = 0.959, NFI = 0.905, TLI = 0.954, and IFI = 0.960 were the model fit outcomes in the validation factor analysis. All of the model fit markers fell within reasonable bounds. Conclusion The Chinese version of the Oncology Nurses Health Behaviors Determinants Scale (HBDS-ON) has good reliability and validity and can be used as a tool to assess the influencing factors of chemotherapy exposure for oncology nurses in China.